Analisis Klaster Keputusan Portofolio Investor Muslim Pemula - Zakiyyah, Amalina Maryam; Kurniawati, Lintang Setyo (Universitas Muhammadiyah Jember, 2025)
The sharia investment industry in Indonesia is growing rapidly along with public awareness of sharia-compliant investments. This study aims to understand the factors that influence stock portfolio decisions and the behavior of novice Muslim investors. For this purpose, data will be collected on financial literacy, tenure, gender, and risk perceptions intervened by religion using a questionnaire. Meanwhile, to collect data on portfolio decisions, a semi-experimental approach will be used which will produce sharia Sharpe ratio values. Cluster analysis is conducted to identify patterns in the data. This analysis helps in understanding the relationship between investor attributes and their stock portfolio decisions. In addition, this analysis can also help researchers identify groups of investors who have similar investment behavior. The results of this study can provide a deeper understanding of the factors that influence stock portfolio decisions and the behavior of novice Muslim investors. The results of this study can be useful for investors, investment managers, and capital market regulators.